Arterial Spin Labeling (ASL) MRI in Evaluating Pancreatic Blood Perfusion in Subjects With Different Glucose Tolerances - Zhang, Yuling; Tao, Zhengzheng; Ji, Qian (Journal of magnetic resonance imaging, 2025)
Background The pancreas plays a central role in type 2 diabetes mellitus (T2DM), and its blood flow is usually associated with insulin release demand. Purpose To noninvasively assess pancreatic blood flow (PBF) changes and modulation in people with different glucose tolerance following a glucose challenge using ASL MRI. Study Type Prospective. Subjects Fourteen prediabetes, 22 T2DM, and 40 normal. Field Strength/Sequence Pseudo‐continuous ASL with a turbo gradient spin echo sequence at 3.0 T. Assessment All normal and subjects (diagnosed by oral glucose tolerance test) underwent ASL after fasting for at least 6 hours. The normal and prediabetes groups additionally had ASL scans at 5, 10, 15, 20, and 25 minutes following oral glucose (50 mL, 5%). PBF maps were generated from the ASL data and measured at body and tail. The ability of baseline PBF (BL‐PBF) of body, tail (BL‐PBFtail), and their average to determine abnormal glucose tolerance and stage was assessed. Statistical Tests ANOVA, Mann–Whitney U test, Kruskal–Wallis H test, paired sample t‐test, intra‐class correlation coefficient, repeated measures ANOVA, correlation analysis, receiver operating characteristic analysis, and logistic regression analysis. A P value <0.05 was considered significant. Results There were significant differences in BL‐PBF among the three groups. The prediabetes group exhibited significantly lower PBF than the normal group at all time points; Both groups showed similar changing trends in PBF (peaking at the 15th minute and subsequently declining). The BL‐PBFtail had the highest diagnostic performance when evaluating abnormal glucose tolerance or stage (area under the curves = 0.800, 0.584, respectively) and was an independent risk factor for glucose tolerance status. Data Conclusion ASL can noninvasively assess changes in PBF among individuals with varying glucose tolerance and in response to glucose challenge, which could be linked to insulin release demand and might help characterize changes in pancreatic endocrine function. Evidence Level 2 Technical Efficacy Stage 1